Literature review Green supply chain management di pelayanan kesehatan - Permatasari, Intan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study is an exploratory study of the drivers and barriers faced by the Healthcare sector in implementing Green Supply Chain Management (GSCM). Interviews and online questionnaire distribution of 15 questions were conducted on 6 selected respondents using the purposive sampling technique. Some drivers and barriers are adopted from previous research and adapted to the field of Healthcare. The results obtained are the highest barrier factors faced by the Pelayanan Kesehatan sector, namely barriers to knowledge and awareness; barriers to technology, economic barriers. Meanwhile, the drivers factor with the highest percentage is government regulation; ISO 14001 certification; and reusing and recycling materials and packaging. The discovery of this factor can provide insight for the Healthcare sector to increase drivers and prevent existing barriers.